Hey!
----------------------------------------------------
Solution:
2x - 3|x + 1| = -2x - 11
2x - 3|x + 1| + (-2x) = -2x - 11 + (-2x)
-3|x + 1| = -4x - 11
-3|x + 1|/-3 = -4x - 11/-3
|x + 1| = 4/3x + 11/3
x + 1 = -(4/3x + 11/3)
x + 1 + 4/3x = 4/3 + -11/3 + 4/3x
7/3x + 1 = -11/3
7/3x + 1 - 1 = -11/3 - 1
7/3x = -14/3
7/3x * 3/7 = -14/3 * 3/7
x = -2
----------------------------------------------------
Check:
2(-2) - 3|-2 + 1| = -2(-2) - 11
(-4) - 3|-1| = (4) - 11
(-4) - 3 = (4) - 11
-7 = -7
----------------------------------------------------
Answer:
x = -2
----------------------------------------------------
Hope This Helped! Good Luck!